Glioma stem cell (GSC)-derived autoschizis-like products confer GSC niche properties involving M1-like tumor-associated macrophages. (11th May 2020) - Tabu, Kouichi; Liu, Wenyu; Kosaku, Akina; Terashima, Kazuo; Murota, Yoshitaka; Aimaitijiang, Alapati; Nobuhisa, Ikuo; Hide, Takuichiro; Taga, Tetsuya
Abstract: Spontaneous necrosis is a defining feature of glioblastomas (GBMs), the most malignant glioma. Despite its strong correlations with poor prognosis, it remains unclear whether necrosis could be a possible cause or mere consequence of glioma progression. Here we isolated a particular fraction of necrotic products spontaneously arising from glioma cells, morphologically and biochemically defined as autoschizis-like products (ALPs). When administered to granulocyte macrophage colony-stimulating factor (GM-CSF)-primed bone marrow-derived macrophage/dendritic cells (Mφ/DCs), ALPs were found to be specifically engulfed by Mφs expressing a tumor-associated macrophage (TAM) marker CD204. ALPs from glioma stem cells (GSCs) had higher activity for the TAM development than those from non-GSCs. Of note, expression of the Il12b gene encoding a common subunit of IL-12/23 was upregulated in ALPs-educated Mφs. Furthermore, IL-12 protein evidently enhanced the sphere-forming activity of GBM patient-derived cells, although interestingly IL-12 is generally recognized as an antitumoral M1-Mφ marker. Finally, in silico analysis of The Cancer Genome Atlas (TCGA) transcriptome data of primary and recurrent GBMs revealed that higher expression of these IL-12 family genes was well correlated with more infiltration of M1-type TAMs and closely associated with poorer prognosis in recurrent GBMs. Our results highlight a role of necrosis in GSC-driven self-beneficial niche construction and glioma progression, providing important clues for developing new therapeutic strategies against gliomas. : Abstract : Strategic necrosis of glioma stem cells (GSCs) to develop GSC-friendly M1-type tumor-associated macrophage.